Nitrogen and oxygen dual-doping on carbon electrodes by urea thermolysis and its electrocatalytic significance for vanadium redox flow battery. (10th July 2020) - Kim, Seong-Cheol; Lim, Hyebin; Kim, Hyebin; Yi, Jung S.; Lee, Doohwan
Abstract: Electrocatalytic properties of graphite felt (GF) electrodes for vanadium redox flow battery (VRFB) are markedly enhanced by the atomic N and O dual-doping via a simple and environmentally-benign urea thermolysis method. A synergetic co-impregnation of GF with urea and polyethylene glycol (PEG) followed by an oxidative thermal treatment results in significant N and O dual-doping on GF surface with high atomic density and structural uniformity. A correlation analysis on the electrocatalytic properties of the electrodes with respect to the elemental contents and configurations of the doped N and O species reveals that (i) the N species afford much greater kinetic enhancements than the O species for the vanadium redox reactions and (ii) the pyrrolic-N and pyridinic-N lattice configurations are the most kinetically relevant active centers. The electrochemical impedance spectroscopy (EIS) studies reveal that the N and O dual-doping markedly reduce the kinetic overpotential of the positive (VO 2+ /VO2 + ) and the negative (V 2+ /V 3+ ) electrode redox reactions. The operando studies on the through-plane voltage losses of the VRFB indicate that the GF electrodes obtained by urea thermolysis significantly reduce the cell voltage losses, particularly on the anode side, which greatly improved the voltage and energy efficiencies and the charge-discharge capacities of the VRFB. Graphical abstract: Image 1 Highlights: N and O atoms are dual-doped on carbon electrodes by urea thermolysis. The properties of electrodes are investigated for vanadium redox flow battery (VRFB). The kinetic relevance of N and O active sites for vanadium redox reactions is identified. Operando studies are conducted in practical operation conditions of VRFB. The N and O dual-doping results in marked enhancement in the vanadium redox kinetic.